IGF-1 and IGFBP-1 in peripheral blood and decidua of early miscarriages with euploid embryos: comparison between women with and without PCOS. (2nd July 2016) - Luo, Lu; Wang, Qiong; Chen, Minghui; Yuan, Guangqing; Wang, Zengyan; Zhou, Canquan
Abstract: This study aims to demonstrate the possible relationship between the insulin-like growth factor (IGF) system and early miscarriage in polycystic ovarian syndrome (PCOS) patients with euploid embryos. 40 pregnant women included. 9 had PCOS and miscarried; 20 had PCOS and a successful ongoing pregnancy; the remaining 11 women did not have PCOS and miscarried. An ultrasound scan was performed to prove clinical pregnancy and a blood sample was taken on day 55 ± 4 of gestation. Serum samples of IGF-1, insulin-like growth factor binding protein-1 (IGFBP-1), total testosterone, serum hormone binding protein (SHBG), leptin and soluble leptin receptor (sOb-R) were obtained. In miscarriages, samples of decidua were obtained during vaccum curettage. Embryonic chromosomes in all miscarriages were proven to be normal. The expression of IGF-1, IGFBP-1, leptin, long-form leptin receptor and androge sOb-R n receptor (AR) were examined in the decidua. We found that miscarried PCOS patients showed significantly increased free androgen index and free IGF index, as well as decreased SHBG and IGFBP-1 than other two groups in peripheral blood. In the decidua, miscarried PCOS patients showed significantly increased expression of IGF-1 and decreased IGFBP-1 when compared with non-PCOS. AR was not expressed in the decidua of either group. Our results suggest that early miscarriage is associated with increased IGF-1 and decreased IGFBP-1 in PCOS patients.